2018
DOI: 10.1038/s12276-018-0114-1
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke extract enhances neutrophil elastase-induced IL-8 production via proteinase-activated receptor-2 upregulation in human bronchial epithelial cells

Abstract: Although inflammation, oxidative stress, and protease-antiprotease imbalance have been referred to as a pathogenic triad in chronic obstructive pulmonary disease (COPD), little is known about how they interact. The objectives of this study were to elucidate the effect of cigarette smoke extract (CSE) on the neutrophil elastase (NE)-induced inflammatory response and its molecular mechanism in bronchial epithelial cells. We observed that NE activated extracellular signal-regulated kinase (ERK) and induced IL-8 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 30 publications
5
30
0
1
Order By: Relevance
“…Our results also revealed that the costimulation of human epithelial cells with CSE þ IL-17A significantly increased the production of IL-17Aeinduced cytokines via an upregulation of IL-17R (Figures 2a and 3), which is consistent with a previous report (Lee et al, 2018). In another study, the IL-17A pathway was activated in the skin lesions of PPP (Bissonnette et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Our results also revealed that the costimulation of human epithelial cells with CSE þ IL-17A significantly increased the production of IL-17Aeinduced cytokines via an upregulation of IL-17R (Figures 2a and 3), which is consistent with a previous report (Lee et al, 2018). In another study, the IL-17A pathway was activated in the skin lesions of PPP (Bissonnette et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…In total, 165 patients with PAO were identified among 576 patients with PPP (28.6%). There were 35 males (21.2%) and The most common location of pain was the anterior chest (n = 134), followed by shoulder (34), lumbar spine (19), knee (14), cervical spine (11), digit (9), ankle (9), sacroiliac joint (8), elbow (5), wrist (5), mandible (2), back (2), sole (1), and heal (1). Technetium bone scintigraphy was performed in 97 cases (97/165: 58.8%).…”
Section: Resultsmentioning
confidence: 99%
“…AhR activation contributes to Th17 differentiation through various intracellular signaling pathways . In addition, cigarette smoke extracts enhanced IL‐17A‐induced IL‐8 production by human bronchial epithelial cells, mediated by upregulation of IL‐17 receptor expression . Thus, Th1/Th17‐type cytokine balance is suggested to play an important role in the pathogenesis of PPP …”
Section: Discussionmentioning
confidence: 99%
“…The high level of neutrophil influx is understood to be a typical characteristic of COPD (56). Neutrophils release a protease that causes damage to the endothelial cells of the airway and accelerates lung destruction (57). Neutrophil-derived ROS lead to oxidative stress in the pathogenesis of lung inflammation and are consistently observed in patients with COPD and COPD animal models (58).…”
Section: Discussionmentioning
confidence: 99%